Compound-Specific Chlorine Isotope Analysis of the Herbicides Atrazine, Acetochlor, and Metolachlor - Lihl, Christina; Torrento Aguerri, Clara; Elsener, Martin; Hunkeler, Daniel (My University, 2018)
A gas chromatography−single quadrupole mass spectrometry method was developed and validated for compound-specific chlorine isotope analysis (Cl-CSIA) of three chlorinated herbicides, atrazine, acetochlor, and metolachlor, which are widespread contaminants in the environment. For each compound, the two most abundant ions containing chlorine (202/200 for atrazine, 225/223 for acetochlor, and 240/238 for metolachlor) and a dwell time of 30 ms were determined as optimized MS parameters. A limit of precise isotope analysis for ethyl acetate solutions of 10 mg/ L atrazine, 10 mg/L acetochlor, and 5 mg/L metolachlor could be reached with an associated uncertainty between 0.5 and 1‰. To this end, samples were measured 10-fold and bracketed with two calibration standards that covered a wide range of δ37Cl values and for which amplitudes matched those of the samples within 20% tolerance. The method was applied to investigate chlorine isotope fractionation during alkaline hydrolysis of metolachlor, which showed a shift in δ37Cl of +46‰ after 98% degradation, demonstrating that chlorine isotope fractionation could be a sensitive indicator of transformation processes even when limited degradation occurs. This method, combined with large-volume solid-phase extraction (SPE), allowed application of Cl-CSIA to environmentally relevant concentrations of widespread herbicides (i.e., 0.5−5 μg/L in water before extraction). Therefore, the combination of largevolume SPE and Cl-CSIA is a promising tool for assessing the transformation processes of these pollutants in the environment.